The end of the middle [telephone industry]. - Isenberg, D.S.
Pushing network intelligence out to its edges is causing the phone industry to fail - and that is okay. Technological changes affecting telephony are so profound that the end of the large incumbent telephone companies is at hand. They will fail or become unrecognizable, as telephone services are embedded in a more general-purpose network - the Internet. The US Telecommunications Act of 1996 was designed to cope with these changes in technology, but it has been an utter failure, in large part because it did not apprehend a pivotal architectural change, the end-to-end principle. The article discusses the implications of the principle and the Internet for the future of the telephone industry.
Keywords: Internet; End-to-end principle; Network intelligence; Technological change; Telephone industry; Telephony